2021
DOI: 10.1097/pas.0000000000001759
|View full text |Cite
|
Sign up to set email alerts
|

High-grade Papillary Early Gastric Carcinoma With High Risk for Lymph Node Metastasis and Poor Prognosis

Abstract: Papillary early gastric carcinoma (EGC) is believed to have a low risk of lymph node metastasis (LNM) and thus can be resected endoscopically. We observed anecdotally that some papillary EGC tumors showed conspicuous high-grade dysplastic features, but the significance of these observations is unknown. In this bicenter study we investigated papillary EGCs that were divided into high-grade (n=96) and low-grade (n=118) groups among 1136 consecutive EGC radical resection cases. Concurrent 464 well-moderately diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The tumor is classified as papillary adenocarcinoma when more than 50% of the tumor area shows papillary structures [ 96 ]. Papillary adenocarcinoma is frequently associated with liver metastasis, a higher rate of LN involvement and poor outcome [ 96 97 98 ].…”
Section: General Considerationsmentioning
confidence: 99%
“…The tumor is classified as papillary adenocarcinoma when more than 50% of the tumor area shows papillary structures [ 96 ]. Papillary adenocarcinoma is frequently associated with liver metastasis, a higher rate of LN involvement and poor outcome [ 96 97 98 ].…”
Section: General Considerationsmentioning
confidence: 99%
“…Previous studies suggested that the differentiated subtypes of GCs usually behaved with lower malignant potential and relatively better prognosis [ 8 10 ]. However, many studies have indicated that PGCs have malignant potential and a higher rate of lymphovascular invasion, lymph node metastasis as well as poorer prognosis [ 11 14 ]. Therefore, preoperatively discriminating PGCs is of importance for clinical treatment decision-making and prognosis estimation.…”
Section: Introductionmentioning
confidence: 99%